2-Pentadecyl-2-Oxazoline, the Oxazoline of Pea, Modulates Carrageenan-Induced Acute Inflammation - Petrosino, Stefania; Campolo, Michela; Impellizzeri, Daniela; Paterniti, Irene; Allarà, Marco; Gugliandolo, Enrico; D’Amico, Ramona; Siracusa, Rosalba; Cordaro, Marika; Esposito, Emanuela; Di Marzo, Vincenzo; Cuzzocrea, Salvatore (Frontiers in Pharmacology, 2017)
N-acylethanolamines (NAEs) involve a family of lipid molecules existent in animal and plant, with N-palmitoylethanolamide (PEA) that arouses great attention owing to its anti-inflammatory, analgesic and neuroprotective activities. Because PEA is produced on demand and exerts pleiotropic effects, the modulation of specific amidases for NAEs (and in particular N-acylethanolamine-hydrolyzing acid amidase NAAA, which is more selective for PEA) could be a condition to preserve its levels. Here we investigate the effect of 2-Pentadecyl-2-oxazoline (PEA-OXA) the oxazoline of PEA, on human recombinant NAAA in vitro and in an established model of Carrageenan (CAR)-induced rat paw inflammation. PEA-OXA dose-dependently significantly inhibited recombinant NAAA and, orally administered to rats (10 mg/kg), limiting histological damage, thermal hyperalgesia and the increase of infiltrating inflammatory cells after CAR injection in the rat right hindpaw, compared to ultramicronized PEA given orally at the same dose (10 mg/kg). These effects were accompanied by elevation of paw PEA levels. Moreover, PEA-OXA markedly reduced neutrophil infiltration and pro-inflammatory cytokine release and prevented CAR-induced IκB-α degradation, nuclear translocation of NF-κB p65, the increase of inducible nitric oxide synthase, cyclooxygenase-2, intercellular adhesion molecule-1, and mast cell activation. Experiments in PPAR-α knockout mice showed that the anti-inflammatory effects of PEA-OXA were not dependent on the presence of PPAR-α receptors. In conclusion, NAAA modulators as PEA-OXA could help to maximize the tissue availability of PEA by increasing its levels and anti-inflammatory effects.